AKUNTABILITAS PELAYANAN SURAT PERINTAH PENCAIRAN DANA PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN MAMUJU UTARA - Mulaningsih, Sri (Katalogis, 2016)
This study aims to determine implementation of the bureaucratic apparatus of accountability Financial Management Board and the Regional AssetÂ  North Mamuju Distric. The research using qualitative descriptive methode. The informant came from the apparatus of bureaucrats on the Financial Management Board and Asset North Mamuju District that consist of Proxy Regional Treasurer, Head of the Sub-Sector Spending, Head of the Sub-Sector Expenditures, officers executing and services of SP2D and also society as a service use. Data collection methods using include observation, interview, documentation. Data analysis techniques include data processing, data reduction, category, checks the validity of the data and drawing conclusions. The theory used is based on the theory of Joko Widodo for the Accountability process, it using three indicators: Compliance Procedure, officers Behavior and Media Accountability. The results using the above theory suggests that adherence to procedures officers bureaucrats BPKAD North Mamuju District, showed that the standard implementation of the activities made sufficient in accordance with Regulation of the Permempan PER-34 / NT / 2006 regarding the disbursement of funds by BPKAD, but in implementation still found any irregularities in its implementation. The behavior of bureaucrats apparatus also shows the ethics of the bureaucratic apparatus still needs to be addressed, this is evidenced by the diversity of the service user feedback on the services they receive. A slow time, a culture of giving "extra" money, inaccuracy and the existence of duplicate tasks received by the bureaucratic apparatus, causing a decrease in the quality of public services. .